Diagnostic of damage in a building of the early twentieth century in Havana. Case study - Oroza, Alberto Hernández; Hernández, Rafael González (Revista ALCONPAT, 2019)
The objective of this work is to diagnostic the existing deterioration in a reinforced concrete building located in Old Havana, Cuba, built in 1906. Due to the years of exploitation and lack of maintenance, the property began to show detachment of concrete and cracks in almost all structural elements. To evaluate the service life, electrical resistivity studies of the concrete were carried out, chemical tests to quantify the levels of free chloride and sulphate, corrosion potential tests, section losses of the reinforcement bars, extractions of concrete specimens and visual analysis of the present damages. The results obtained showed that although the building presents an advanced deterioration, it can be rehabilitated, and it is possible to extend its service lifetime.